HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP TERHADAP PERILAKU CUCI TANGAN PAKAI SABUN DALAM PENCEGAHAN COVID-19 DI SMAN 64 JAKARTA TAHUN 2021 - Hikmah Nur Sholehati (2021)
Background: Washing hands with soap is one of the indicators in the Clean and Healthy Behavior (PHBS) program in schools and its community. This behavior is a basic protection in efforts to prevent the transmission of COVID-19, in the last three months there has been an increasing in DKI Jakarta, which initially had 995 cases on July, 16th 2020 and then reached 1.976 cases of youth aged 6-19 years old as of September, 30th 2020. Youth's behavior in washing hands can be influenced by several factors such as knowledge and attitudes about washing hands with soap. This study aims to determine the relationship between the level of knowledge and attitudes towards washing hands with soap in preventing COVID-19 at SMAN 64 Jakarta. Methods: This research was an observational analytic study with cross sectional research design, the population were all students of SMAN 64 Jakarta, amounting to 755 students. The samples in this study were 93 students of class X, XI, and XII who were taken using a proportional stratified random sampling technique. Data obtained by distributing questionnaires and filled out directly by students. Data analysis techniques using the Chi-square test. Results: based on the chi-square test with a degree of trust (95%), it is shown that there is a relationship between the level of knowledge towards washing hands with soap (p = 0.000). There is a relationship between attitudes towards washing hands with soap (p = 0.000). Conclusion: Students with a good level of knowledge and attitude have a greater possibility to do handwashing with soap. Students' knowledge and attitudes can be improved by educating them about proper hand washing from the school in collaboration with related parties and increasing the provision of hand washing facilities in schools.